Sitthi prayōt kh̨̄ong phū kīeokh̨̄ong kap wongngān Ratthasaphā (K̨̄ong Kānprachāsamphan, Samnakngān Lēkhāthikān Saphā Phūth̄æn Rātsad̨̄on, 1996)
On salaries and benefits of employee's of National Assembly, Thailand.